EFFECT OF INTERACTION BETWEEN PROCESSING METHODS AND LEVEL OF INCLUSION OF PROCESSED-FERMENTED JATROPHA CURCAS (L) KERNEL MEALS ON THE PERFORMANCE OF FINISHER BROILER CHICKENS - Ojediran, Taiwo K; Ajayi, Ayodeji Folorunso; Emiola, Isiak Adewale (Journal of Agricultural Sciences (Belgrade), 2019)
Three hundred 21-d old broiler chicks were reared using a 3 x 3 factorial model in a completely randomized design with 10 treatment groups having 3 replicates of 10 birds each. The birds were raised on a commercial starter diet at the starter phase before being allotted into dietary groups in a 21-d feeding trial at the finisher phase. The interaction between treatment and varying inclusion levels of processed-fermented Jatropha curcas (L) kernel meals (JKM) on the performance of broiler chicks was investigated. Jatropha curcas kernels were subjected to three different processing methods, namely: Raw Defatted Fermented Meal (RDFM), Cooked Defatted Fermented Meal (CDFM) and Lye treated Defatted Fermented Meal (LDFM). Each meal was included at varying inclusion levels of 2.5%, 5.0% and 7.5% such that Diet 1 (control) contained 0% JKM while diets 2, 3, 4, contained 2.5%, 5.0% and 7.5% RDFM, diets 5, 6, and 7 contained 2.5%, 5.0% and 7.5% CDFM and diets 8, 9, 10 contained 2.5%, 5.0% and 7.5% LDFM. Feeding differently processed-fermented JKM to these broilers does not (p>0.05) compromise the feed conversion ration. Although, the results indicated an improvement (p